2014
DOI: 10.1007/s11096-014-9917-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clinical pharmacist intervention on medication discrepancies following hospital discharge

Abstract: Background Medication discrepancies may occur at transitions in care and negatively impact patient outcomes. Objective To determine if involving clinical pharmacists in hospital care, medication reconciliation and discharge medication plan communication can reduce medication discrepancies with a prospective, randomized, blinded, controlled trial. Setting A large, tertiary care, academic medical center. Method The intervention consisted of clinical pharmacist medication reconciliation, patient education a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 19 publications
0
64
0
3
Order By: Relevance
“…5 In their study of elderly patients, Budnitz and others 6 found that nearly twothirds (65.7%) of hospital admissions through the emergency department were due to unintentional overdoses. Coleman and others 7 found that medication discrepancies led to a statistically significant increase in the readmission rate (14.3% versus 6.1%, p = 0.04). Even more alarming is research suggesting that many of these ADRs are avoidable : across numerous studies, 14% to 50% of ADRs were avoidable and up to 75% were ameliorable.…”
Section: The "Pro" Sidementioning
confidence: 88%
See 1 more Smart Citation
“…5 In their study of elderly patients, Budnitz and others 6 found that nearly twothirds (65.7%) of hospital admissions through the emergency department were due to unintentional overdoses. Coleman and others 7 found that medication discrepancies led to a statistically significant increase in the readmission rate (14.3% versus 6.1%, p = 0.04). Even more alarming is research suggesting that many of these ADRs are avoidable : across numerous studies, 14% to 50% of ADRs were avoidable and up to 75% were ameliorable.…”
Section: The "Pro" Sidementioning
confidence: 88%
“…The provision of postdischarge follow-up care by pharmacists reduces the number of preventable adverse drug events and medication discrepancies 30 days after discharge, but may not affect the total number of adverse drug events or total health care utilization and does not appear to have a sustained effect on medication discrepancies. 3,7 Some studies have indicated that postdischarge medication reviews by a pharmacist may improve outcomes in specific patient populations, 8,9 but other studies have shown no improvement in clinically important outcomes, health care utilization, adverse events, or adverse drug events among those who received enhanced care, including postdischarge follow-up by a pharmacist, relative to those who received standard seamless care at discharge. 10,11 Also, it is currently unclear what this follow-up care should encompass.…”
Section: The "Con" Sidementioning
confidence: 99%
“…The enhanced intervention group was found to have a statistically significant lower number of medication discrepancies 30 days after discharge, which suggested that pharmacist involvement helped to improve the accuracy of the patients' electronic medical record, which can be accessed throughout the hospital system [6].…”
Section: Pharmacist Integration Into Transitions Of Care At a Communimentioning
confidence: 95%
“…Skilled Nursing Facility Discharges 438 et al [6] researched two different levels of pharmacist involvement at discharge compared to a control group in order to improve communication between the hospital and primary care physicians in the community. The enhanced intervention group was found to have a statistically significant lower number of medication discrepancies 30 days after discharge, which suggested that pharmacist involvement helped to improve the accuracy of the patients' electronic medical record, which can be accessed throughout the hospital system [6].…”
Section: Pharmacist Integration Into Transitions Of Care At a Communimentioning
confidence: 99%
“…We did not aim to study the effect of individual modules or to evaluate the benefit of medication checks; other studies have already done so (1,2). Studies that were conducted in non-German speaking countries have shown that multifactorial problems at interfaces can be solved quickly by combining several measures in medication management (3). By pointing out that the information event was not an intervention we intended to clarify that no substantial recommendations were given there-for example, on prescribing after discharge-but only information on the organizational approach to the structure and mailing of the discharge medication plan.…”
Section: In Replymentioning
confidence: 99%